2010
DOI: 10.1007/s11060-010-0290-x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating markers of angiogenesis, inflammation, and coagulation in patients with glioblastoma

Abstract: Inflammation, angiogenesis, and coagulation are linked to the development of cancer. In glioblastoma, microvascular proliferation is a hallmark, and lymphocytic infiltration is a common finding. Thromboses are frequent in patients with glioblastoma. The objective of this study was to assess presurgical levels of circulating markers of inflammation, angiogenesis, and coagulation in a prospective series of patients with glioblastoma, and to explore their correlations and possible associations with clinical findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
86
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 28 publications
8
86
0
Order By: Relevance
“…Albumin is a recognized 'negative' acute phase protein with serum levels inversely related to the magnitude of the systemic inflammatory response as a consequence of increased catabolism and downregulation of hepatic synthesis, primarily by the cytokines TNFa and IL-6 [19]. Patients with GBM have significantly higher levels of circulating IL-6 compared with normal controls [20]. Moreover, amplified IL-6 gene expression has been confirmed in glioblastoma tumour cells [21], and has been shown to correlate inversely with survival [22].…”
Section: Discussionmentioning
confidence: 99%
“…Albumin is a recognized 'negative' acute phase protein with serum levels inversely related to the magnitude of the systemic inflammatory response as a consequence of increased catabolism and downregulation of hepatic synthesis, primarily by the cytokines TNFa and IL-6 [19]. Patients with GBM have significantly higher levels of circulating IL-6 compared with normal controls [20]. Moreover, amplified IL-6 gene expression has been confirmed in glioblastoma tumour cells [21], and has been shown to correlate inversely with survival [22].…”
Section: Discussionmentioning
confidence: 99%
“…IRF-1 was the third hit of the list. In general, there were several correlations with genes of the IFN response (USP18, ISG20, ISG15) thus possibly indicating that in the selected tumors an inflammatory response was engaged [25].…”
Section: The Spontaneous Ifn-signaling Supports Trail Expression In Tmentioning
confidence: 98%
“…We recently developed specific ELISAs for OPN-R and OPN-L and demonstrated that these cleaved OPN forms are markedly elevated in the synovial fluid of patients with rheumatoid arthritis but not osteoarthritis or psoriatic arthritis, validating its significance in vivo (25). Thrombin activation is increased in patients with GBM as shown by the elevation of prothrombin fragment F1 ϩ 2 in their plasma (27), and intravascular thrombosis has been suggested to be involved in progression of astrocytomas to GBMs (28).…”
mentioning
confidence: 96%